Analisys STRATEGI PEMASARAN PT. SUKSES INTERNASIONAL TOUR & TRAVEL DALAM MENGHADAPI PERSAINGAN BISNIS HAJI DAN UMRAH DI BUKITTINGGI: STRATEGI PEMASARAN PT. SUKSES INTERNASIONAL TOUR & TRAVEL DALAM MENGHADAPI PERSAINGAN BISNIS HAJI DAN UMRAH DI BUKITTINGGI - Maharani, Tetti; Nurani, Khadijah (Fakultas Ekonomi dan Bisnis Universitas Satya Negara Indonesia, 2025)
ABSTRACT Marketing strategy is a fundamental tool designed to achieve company goals by developing sustainable competitive advantages to enter the market and serve predetermined target markets. The increasing public interest in carrying out the Hajj and Umrah has resulted in Hajj and Umrah travel popping up in Bukittinggi. Therefore, PT. Successful International Tour & Travel needs to develop a good marketing strategy in order to face competition in the Hajj and Umrah business in Bukittinggi. The purpose of this research is to find out how the marketing strategy of PT. Success of International Tour & Travel in Facing Hajj and Umrah Business Competition in Bukittinggi. This type of research is qualitative research carried out at PT. Success of International Tour & Travel Bukittinggi through observation, interviews and documentation regarding research objects. The data analysis technique used in this research is SWOT analysis. The results of research conducted at PT. Bukittinggi Tour & Travel International Success: Marketing Strategy Development carried out by PT. International Tour & Travel's success in facing competition in the Hajj and Umrah business in Bukittinggi is using the SO strategy, namely (1) Providing varied packages (2) Offering various prices according to facilities (3) Providing satisfactory service (4) Providing quality human resources (5) Providing complete facilities and infrastructure.